Night lighting and anthropogenic noise alter the activity and body condition of pinyon mice (Peromyscus truei). Issue 3 (4th March 2021) - Willems, Joshua S.; Phillips, Jennifer N.; Vosbigian, Ryan A.; Villablanca, Francis X.; Francis, Clinton D.
Abstract: Anthropogenic noise and artificial night lighting have been shown to have substantial effects on animal behavior, physiology, and species interactions. Despite the large body of previous work, very few studies have studied the combined effects of light and noise pollution, especially experimentally in the field. Rodents are a highly diverse group that are predominantly nocturnal and occupy a wide range of habitats worldwide, frequently in close association with human development, placing them at a heightened risk from sensory disturbances. To test the singular and combined effects of various levels of anthropogenic light and noise exposure on pinyon mouse ( Peromyscus truei ) activity and body condition, we used standard trapping methods across a gradient of light and noise and the two combined and accounted for variation of moonlight, vegetation structure, and weather. We hypothesized that increased levels of artificial light would decrease trap success and lead to lower body condition due to an increase in perceived predation risk and that increased noise levels would increase trap success and body condition due to a reduction in predation risk and/or release from competition. Pinyon mouse trap success declined as light intensity increased, and the effect was comparable to that of moonlight, which is well known to influence rodent activity and perception of predation risk. Although noise pollution did not alter trap success of pinyon mice, individuals captured in noisier areas at the beginning of the season had lower body condition than those from quieter areas. Body condition was uninfluenced by noise and light later in the season. We also found no evidence of any additive or synergistic effects of the two stimuli. Our results provide evidence that alterations to the sensory environment from anthropogenic activity can affect wild rodents in several ways. As anthropogenic development increases to meet the demands of growing human populations, more ecosystems will be exposed to increased levels of sensory disturbance, making the understanding of how these changes affect wildlife critical to ongoing conservation efforts.